The use of Electrical Resistivity Tomography and Induced Polarization to investigate seepage conditions in a Hydroelectric Dam (A case study of the East Dike of the Kpong Hydro Dam) - Dery, Clement Yizaa (2021)
A thesis submitted to the Department of Geological Engineering (Faculty of Civil and Geo-Engineering) College of Engineering in partial fulfilment of the requirements for the degree of Master of Science (Geophysical Engineering)